Platform Work: Mapping Debates and Concepts - Breznik, Maja; Turnšek, Maja (Journal for Geography, 2023)
This article provides a mappping of scientific debates on platform work, focusing on their concepts. The explosive growth of platform work has produced a number of scientific contributions worldwide. In this review, we are interested in how scholars process their 'raw material' and how they define their 'object of knowledge' when they challenge the self-image of platforms as 'technological enterprises', supposedly a net result of automation, robotization, the sharing economy and the fourth industrial revolution. The review has identified five key concepts for understanding work in ICT-driven environments: platform urbanism, digital Taylorism, regulatory arbitrage, planetary labour markets and heteromatised labour. In the conclusion, we present the echo of these debates in social responses.